PENGARUH MEDIA PERMAINAN SNAKE LEADER CARD (SLC) TERHADAP PENGETAHUAN DAN SIKAP TENTANG DBD : Indonesia - Farhand; Marsofely, Reka Lagora; Sumaryono, Dino (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2023)
Dengue Hemorrhagic Fever (DHF) a viral disease with a mosquito vector that spreads the fastest in the world. This disease is caused by the dengue virus which is transmitted by mosquitoes from the family Flaviviridae, namely Aedes aegepty, Aedes albopictus, and several other Aedes species. This study aims to determine the effect of Snake Leader Card (SLC) game media on knowledge and attitudes about DHF in SD Negeri 76 Bengkulu City. This type of research Pre Experimental with a one group pretest-posttest research design. The sample in this study were students of SD Negeri 76 Bengkulu City, totaling 32 people a simple random sampling technique with a lottery technique with sampling using the lameshow formula. Data analysis in this study used the Wilcoxon signed rank test. The results of the study obtained an average knowledge before 8.50 and after 13.2 while the average attitude before and after was 46.4 and 56.6. The results of the Wilcoxon signed rank test obtained p value = 0.000 < 0.005 which shows that there is an influence of Snake Leader Card (SLC) media on knowledge and attitudes about DHF in SD Negeri 76 Bengkulu City. This research is expected to be an alternative choice of health intervention for health promoters in conveying information about DHF, so as to prevent the occurrence of DHF in children. Keywords : Snake Leader Card (SLC), knowledge and attitude DBD